2017
DOI: 10.7759/cureus.1686
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidities and Outcomes in Epilepsy Patients: An Insight from a Nationwide Inpatient Analysis in the United States

Abstract: BackgroundPsychiatric comorbidities in epilepsy impose significant burdens on patients and their families. It affects their quality of life and medical care and results in cost increases. This study reports the impact of various psychiatric comorbidities in epilepsy patients regarding hospital outcomes and in-hospital mortality.MethodsWe used the Nationwide Inpatient Sample (NIS) from the Healthcare Cost and Utilization Project (HCUP) from years 2013-2014. We identified epilepsy as the primary diagnosis and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
1
37
0
3
Order By: Relevance
“…As per the 2015 National Health Interview Survey, epilepsy prevalence is about 1.2% in the United States general population, and our study patients with a primary diagnosis of epilepsy constituted 0.97% of the total inpatient admissions. A nationwide inpatient study estimated 7.8% prevalence of drug abuse in epilepsy patients, which was similar to that seen in our study population (7%). Younger male and non‐Hispanic Black had a higher prevalence of epilepsy hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…As per the 2015 National Health Interview Survey, epilepsy prevalence is about 1.2% in the United States general population, and our study patients with a primary diagnosis of epilepsy constituted 0.97% of the total inpatient admissions. A nationwide inpatient study estimated 7.8% prevalence of drug abuse in epilepsy patients, which was similar to that seen in our study population (7%). Younger male and non‐Hispanic Black had a higher prevalence of epilepsy hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…16 in one more study done by Patel et al ,depression is the most prevalent psychiatric comorbidity in epilepsy. 20…”
Section: Discussionmentioning
confidence: 99%
“…21 A recent study using national US data found that epilepsy patients with comorbid depression or psychosis contributed to higher total hospitalization charges. 26 Psychiatric comorbidities are not only associated with a lack of response to antiseizure Note: Unadjusted model tests association between discharge disposition and epilepsy without controlling for any other factors and without accounting for IPTW.…”
Section: Discussionmentioning
confidence: 99%